Synthesis of Dendritic Silver Nano Powder Using Pulsing Electrolysis in Ammonia Solution - Ali Soltanzadeh; Shayan Shahini; Fereshteh Rashchi; Mojtaba Saba (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
A method of producing nano silver structures with high purity is pulsing electrolysis. In this paper the effects of potential, ammonia concentration (NH3), silver ion concentration [Ag+], total time, Ton, Toff and Trev on this process were studied. The considered parameters were varied as follows: electrical potential = 5 – 10 V; [NH3] = 40 – 80 g/L; [Ag+] = 0.1 – 0.5 g/L; total time = 15 – 30 min; Ton = 1 – 8 ms; Toff = 1 – 8 ms; and Trev = 0 – 4 ms. To optimize these parameters, fractional factorial design of experiments was used. A silver dendritic structure was produced with nano size arm. The phase composition and morphology of the as synthetized dendritic silver nanostructures was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The optimum condition was found at potential of 7.52 V; [NH3] = 64.75 g/L; [Ag+] = 0.45 g/L; total time = 17.59 min; Ton = 6.97 ms; Toff = 4 ms; and Trev = 1.89 ms. A mathematical model was also presented. The predicted silver nano size dendrite arm at the optimum condition was found to be 87.29 nm which was very close to the experimental value of 90 nm.